Effects of surface electrical stimulation during sitting on pelvic floor muscle function and sexual function in women with stress urinary incontinence - Ui-Jae Hwang; Oh-Yun Kwon; Min-Seok Lee (Obstetrics & Gynecology Science, 2020)
ObjectiveDysfunction of the pelvic floor muscles (PFM) is associated with sexual dysfunction in women with stress urinary incontinence (SUI). The EasyK7 device was developed to stimulate the PFM by surface electrical stimulation during sitting (SESdS). We investigated the effects of SESdS on PFM function and sexual function in women with SUI.MethodsWomen with SUI were randomized into the SESdS and control groups. PFM function and sexual function were assessed using a perineometer and the pelvic organ prolapse–urinary incontinence sexual function questionnaire (PISQ), respectively. After 8 weeks, the groups were compared using either analysis of covariance with the baseline values as covariates or the paired Student's t-test.ResultsThe final analysis included 16 subjects from each group. There were significant differences between the SESdS and control groups after the intervention, as well as within the SESdS group between the pre- and post-intervention measurements. The P-values for the differences in PFM measurements between the groups, and between the pre- and post- intervention measurements within the SESdS group, were 0.001 and 0.004 for power, 0.015 and 0.011 for strength, and 0.012 and 0.034 for endurance, respectively. In addition, in the PISQ, there were significant differences between the groups and between the pre- and post-intervention measurements within the SESdS group in the partner-related domain (between groups: P=0.003; within SESdS group: P=0.024) and total score (between groups: P<0.001; within SESdS group: P=0.001).ConclusionSESdS can improve PFM function and sexual function in women with SUI.Trial RegistrationClinical Research Information Service Identifier: KCT0003357